PHONETIC REPEAT: LINGUPOETIC ANALYSIS AND METHODOLOGICAL POSSIBILITIES (Eureka Journal of Language, Culture & Social Change, 2026)
The article contains phonetic repetitions, their application in Mirtemir's poetry and a specific stylistic. The semantic-stylistic features of repetition of alliterations are represented.
Keywords: Repetition, phonetic repetition, alliteration, assonance, gemination, stylistic task.